2024
DOI: 10.1002/smll.202309785
|View full text |Cite
|
Sign up to set email alerts
|

An Ultrasensitive Ti3C2Tx MXene‐based Soft Contact Lens for Continuous and Nondestructive Intraocular Pressure Monitoring

Zhongyi Duan,
Miao Yuan,
Zhiduo Liu
et al.

Abstract: Wearable soft contact lens sensors for continuous and nondestructive intraocular pressure (IOP) monitoring are highly desired as glaucoma and postoperative myopia patients grow, especially as the eyestrain crowd increases. Herein, a smart closed‐loop system is presented that combines a Ti3C2Tx MXene‐based soft contact lens (MX‐CLS) sensor, wireless data transmission units, display, and warning components to realize continuous and nondestructive IOP monitoring/real‐time display. The fabricated MX‐CLS device exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…15,16 Therefore, fabricating wearable ocular devices for continuous IOP monitoring could help prevent glaucoma through early detection and avoid vision loss. 17,18 To meet the requirement of continuous IOP monitoring, the wearable ocular devices must at least comprise two components, namely, energy supply and IOP sensor. 19 Recently, Park et al reported on a hemispherical integrated sensing system to detect the IOP change, where the rigid chip is introduced in the integrated system to power the IOP strain sensor.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Therefore, fabricating wearable ocular devices for continuous IOP monitoring could help prevent glaucoma through early detection and avoid vision loss. 17,18 To meet the requirement of continuous IOP monitoring, the wearable ocular devices must at least comprise two components, namely, energy supply and IOP sensor. 19 Recently, Park et al reported on a hemispherical integrated sensing system to detect the IOP change, where the rigid chip is introduced in the integrated system to power the IOP strain sensor.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, we fabricated a piezoresistive sensor using the principle of a four-wire resistance measurement. Compared to wheatstone bridge piezoresistive sensors, 18 this piezoresistive sensor based on the four-wire method is simple and can eliminate interference of wire resistance, especially for measuring very small resistance. Through testing, we found that the sensor showed excellent sensitivity, linearity, stability, reversibility, and high accuracy.…”
mentioning
confidence: 99%
“…Due to this emerging need, a variety of wearable and implantable IOP sensors have been proposed. Among them, IOP sensors based on microfluidic technology have become an emerging branch in this field. This is because these sensors are typically made from elastic materials such as polydimethylsiloxane (PDMS) , and Ecoflex, which offer natural advantages in terms of flexibility, biocompatibility, and breathability, making them ideal for the fabrication of biosensors.…”
mentioning
confidence: 99%